Highly Efficient Pertraction of Tetravalent Neptunium Ions Across a Flat Sheet Supported Liquid Membrane Containing Two Different Aza-Crown Ether-Based Multiple Diglycolamide Ligands. Issue 2 (23rd February 2023) - Mahanty, Bholanath; Mohapatra, Prasanta K.; Egberink, Richard J. M.; Huskens, Jurriaan; Verboom, Willem
ABSTRACT: Pertraction of Np(IV) across a PTFE membrane containing two different aza-crown ether-based multiple diglycolamide (DGA) ligands termed as L I (3 DGA arms) or L II (4 DGA arms) was investigated using nitric acid as feed solution. A few of the studies were also carried out with Pu(IV) for comparison purposes. The kinetics of the extraction of Np(IV) and Pu(IV) was fast at 3 M HNO3 and within 10 min reaches the equilibrium distribution ( D ) ratio with both ligands. However, the stripping kinetics was slower especially with ligand L II . The extraction and transport studies were carried out using 1.0 × 10 −3 M ligand solution in 95% n -dodecane + 5% isodecanol. The transport rates were slower with ligand L II than with L I at higher nitric acid concentrations (>1 M HNO3 ) and the transport rates decreased with nitric acid concentration with both ligands. The effective diffusion coefficients ( D eff ) of Np(IV) were estimated using the lag-time method as 6.2 × 10 −8 cm 2 s −1 (L I ) and 4.6 × 10 −8 cm 2 s −1 (L II ). The stability data suggest that the L I containing supported liquid membrane (SLM) is comparatively more stable than that of L II and the transport flux remains the same up to nine days of operation in case of ligand L I .